Real-world experience of the role of 18F FDG PET-computed tomography in chronic spinal implant infection. Issue 8 (August 2020) - Brown, Philip H.; Carter, Joseph R.; Moyade, Pamela; Mohammed, Mohammed; De Matas, Marcus; Vinjamuri, Sobhan
Abstract : Objectives: The presence of postinstrumentation back pain in patients after undergoing spinal surgery is a well established phenomenon. So too is the presence of infection, both overt and subclinical which can be a source of pain. The accurate assessment of infection in patients with spinal implants in situ and no overt radiological or biochemical abnormalities frequently presents a diagnostic challenge. We present our experience spanning 5 years of using 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography (18F FDG PET)-computed tomography (CT) scans to aid the diagnostic process in treating presumed low-grade chronic implant infection. Methods: We undertook a retrospective analysis of all patients with spinal implants in place who were referred for 18F FDG PET-CT imaging over a 5-year period. All available images, case notes and laboratory results were reviewed. Results: Data pertaining to 49 patients were analysed, with infection diagnosed on 18F FDG PET-CT in 24 (45%) of those sent for scanning. Fifteen patients in the cohort underwent revision surgery, and 11 of whom had been diagnosed as infected on PET-CT. Confirmation of infection with positive microbiological sampling occurred in 8/11 giving a positive predictive value of 0.72 in our series. Conclusion: We present a real-world experience of using 18F FDG PET-CT as a diagnostic tool in the evaluation of patients with chronic pain after undergoing spinal implantation. We have found PET-CT to be a promising modality and would recommend multicentre collaboration to ensure reproducibility across more centres.